Effect of Spacing and Different Levels of Phosphorus on Growth and Yield of Malepatan-1 Variety of Cowpea (Vigna unguiculata (Linn.) Walp.) in Dang District, Nepal - Biraj Poudel; Gaurab Chaudhary; Archana Bhatt; Shobita Neupane (Advances in Agriculture)
The simplest strategy to boost cowpea production is to have an optimum fertilizer level and spacing. The study was performed to assess the effect of variable row spacing and phosphorus (P) levels on the growth and yield of cowpeas. The experiment was carried out using a split-plot design with three planting geometry as the main plot (15 cm × 30 cm, 30 cm × 30 cm, and 45 cm × 30 cm) and three P levels as subplots (20, 40, and 60 kg/ha), each replicated three times. The result demonstrated that P had a significant effect on the number of pods per plant at 100 days after sowing (DAS), pod length at 85 and 100 DAS, and yield of fresh pods. However, P did not significantly impact plant height or number of pods per plant at 70 and 85 DAS. The highest fresh pod yield (1.05 t/ha) and pod length at 85 and 100 DAS (20.33 and 21.16 cm, respectively) were observed at 60 kg/ha P level. Similarly, the highest number of pods per plant at 100 DAS (8.3) was recorded at a P level of 40 kg/ha, which was comparable to that obtained at a P level of 60 kg/ha (8.1). Also, the spacing showed a nonsignificant effect on any of the studied parameters, except for the number of branches per plant at 30 DAS. The 45 cm × 30 cm spacing resulted in the highest number of branches per plant at this stage (2.4).